Assessment On Morbidity Profile And Quality Of Life Among Homemakers At Selected Slums (Journal of Pharmaceutical Negative Results, 2022)
A major component of health is defined as a state of wellbeing in which the individual realizes his or her abilities can cope with the normal stresses of life can work productively and profitably and is able to make a contribution to his or her community. The main aim of this study is to assess the morbidity profile and quality of life among makers at selected slum. Methodology-The study design was descriptive non-experimental design. total 60 home makers were selected for data collection. A Non-probability purposive sampling technique was used to collect data from the samples. In order to assess the structured interview schedule and WHOQOL-BREF instrument for quality of life. Reliability was calculated by test-retest method which is found 0.82. Result- The major finding showed that the majority of 27(45%) of women were age group from 20-35 years, 27(45%) are primary, 21(35%) having 5001to15000 monthly income, 35 (58.33%) women are Hindu, 24(40%) are living in nuclear family. Most of the home maker’s having some kind of morbidity profile. Majority of 34(56.6%) having Average level of quality of life, the remaining 15(25%) having poor level of quality of life, 11(18.33%) having good level of quality of life. The mean of quality of life of homemakers are 64.33±15.48. The correlate the morbidity profile and quality of life among homemakers the value of r is -0.1943 that shows negative correlation. Conclusion -There will be a no significant association between the selected demographic variables and the morbidity profile and quality of life among home makers at selected slum areas of Pune. Accept the age of home makers showed significant association between the selected demographic variables and the morbidity profile and quality of life. Thus null hypothesis is rejected and research hypothesis